Community Assistance to Achieve Outpatient Services that are Easily Accessible and Understandable - Aya Sofia Diaz; Regina Elianda Tampubolon; Sri Ulina Purba; Nurainun Badriani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Outpatient services are one of the most widely used health services by the public, but various obstacles still arise in their utilization due to lack of understanding of service flow, administrative requirements, and registration mechanisms. This condition has the potential to hinder public access to effective and efficient health services. This community service activity to improve public understanding outpatient services easily accessible, understandable through educational and mentoring activities. The activity was carried in Lubuk Pakam I and II Villages on May 21–23, 2026, with 15 participants. The method used a participatory-educational approach that included identifying community needs, developing educational media, interactive counseling, mentoring through service flow simulations, evaluation using pre-test and post-test instruments. The educational media used were leaflets, posters, presentation slides, and outpatient service flow simulations. The results of the activity showed an increase in participants' knowledge after participating in the mentoring. The average pre-test score of 58.0 increased to 87.0 in the post-test, with an average increase of 29 points. All participants experienced improved scores, indicating that the educational and mentoring methods implemented were effective in increasing public understanding of outpatient care procedures, from administrative requirements and registration mechanisms to the stages of obtaining healthcare services. In addition to increasing knowledge, this activity also encouraged active community participation in understanding and utilizing healthcare services more independently. Therefore, this community service activity has been proven to increase public literacy regarding outpatient care and can be an educational strategy that supports realization accessible, understandable, and community-oriented healthcare services.